1983
DOI: 10.1085/jgp.82.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Simple shifts in the voltage dependence of sodium channel gating caused by divalent cations.

Abstract: The effect of elevated divalent cation concentration on the kinetics of sodium ionic and gating currents was studied in voltage-clamped frog skeletal muscle fibers . Raising the Ca concentration from 2 to 40 mM resulted in nearly identical 30-mV shifts in the time courses of activation, inactivation, tail current decay, and ON and OFF gating currents, and in the steady state levels of inactivation, charge immobilization, and charge vs. voltage. Adding 38 mM Mg to the 2 mM Ca bathing a fiber produced a smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 23 publications
7
54
1
Order By: Relevance
“…This fact provides us with a tool to test the validity of the screening hypothesis. In our study we used the strontium ion (Sr 2þ ) as probe, because it seems to act exclusively via a screening mechanism; together with the magnesium ion (Mg 2þ ), it shifts the G(V) curve less than other tested metal ions, and activation time courses, deactivation time courses, gating currents, and G(V) curves are equally affected, as if these metal ions only alter the membrane voltage (11,15,21,22,(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…This fact provides us with a tool to test the validity of the screening hypothesis. In our study we used the strontium ion (Sr 2þ ) as probe, because it seems to act exclusively via a screening mechanism; together with the magnesium ion (Mg 2þ ), it shifts the G(V) curve less than other tested metal ions, and activation time courses, deactivation time courses, gating currents, and G(V) curves are equally affected, as if these metal ions only alter the membrane voltage (11,15,21,22,(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…Among the ions that can play a role, one of the most effective in screening is calcium [7]. The variation of extracellular free calcium leads to a different screening effect on the outer side of the membrane and this in turn leads to a change in the voltage drop across the membrane, that voltage dependent channels sense and respond to [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, early calculations 66 suggested that 1 mM of a divalent ion added to 100 mM electrolyte could shift membrane potential by ~26 mV due to the screening effect. With these considerations in mind, classical studies of ion channels have routinely documented voltage-dependent channel properties over a range of divalent ion concentrations [67][68][69] . It would seem important for the electrophysiological observations of today to account for such phenomena.…”
mentioning
confidence: 99%